Jesse Jackson - Jakoubek, Robert E.; Huggins, Nathan Irvin, 1927- (New York : Chelsea House, 1991)
Examines the life and political career of Jesse Jackson.
"Civil rights leader and politician"--Cover.
Includes bibliographical references (p. 124) and index.
Booklist.
School Library Journal.
Wilson's Junior High School.
7.3
Keywords: Jackson, Jesse, -- 1941- -- Juvenile literature; Jackson, Jesse, -- 1941-; Jackson, Jesse, -- 1941-; African Americans -- Biography -- Juvenile literature; Civil rights workers -- United States -- Biography -- Juvenile literature; Presidential candidates -- United States -- Biography -- Juvenile literature; African Americans -- Biography; Civil rights workers; African Americans -- Biography; Civil rights workers -- Biography